Rumen fermentative metabolomic and blood insights into the effect of yeast culture supplement on growing bulls under heat stress conditions - Zhang, Xian; Liang, Huan; Xu, Lanjiao; Zou, Bicheng; Zhang, Tingzhou; Xue, Fuguang; Qu, Mingren (Frontiers in Microbiology, 2022)
This study was conducted to investigate the effects of yeast culture supplement on the physiological state and growth performance of growing bulls under heat stress conditions and the underlying mechanism. Fourteen (6.0±1.0 months old) growing bulls with the similar body wight were randomly assigned into the control group (YC0g/d), and yeast culture supplement group (YC40g/d). YC0g/d contained 3 replicates, with 2 bulls in each replicate, which were fed a basal diet. Meanwhile, YC40g/d treatment contained 4 replicates, with 2 bulls in each replicate, which were fed a basal diet supplemented with 40g/day of yeast culture per cattle. Growth performance, nutrient digestibility, rumen fermentable metabolites, serum immunity, serum hormones and serum antioxidant parameters were measured. Results showed the average daily gain significantly increased (P<0.05), while the feed to gain ratio significantly decreased (P<0.01) after YC supplement compared with the YC0g/d. The digestibility of neutral detergent fiber (P<0.05) were higher in YC40g/d. There were no significate differences in ruminal pH, NH3-N, butyrate or acetate/propionate (P>0.05). Besides, the rumen MCP, acetate, propionate and total VFA content remarkably increased with the supplement of YC (P<0.05). Yeast culture supplementation increased the concentration of nicotinamide riboside, neuromedin B, peptides, formyl-5-hydroxykynurenamine. The YC40g/d group had significant (P<0.05) higher serum triiodothyronine level, serum glutathione peroxidase levels and total antioxidant capacity, while the lower serum malondialdehyde level than the YC0g/d group. In conclusion, the addition of yeast culture in the diet improves the growth performance of growing bulls under heat stress by increasing the nutrient digestibility, rumen fermentation function, antioxidant capacity, and rumen metabolites.